DIASPORA AND IDENTITY IN THE DIGITAL AGE: CULTURAL COMMUNITIES AND THE NATION - PEDNEKAR-MAGAL, Vandana (Studia Universitatis Babeș-Bolyai Ephemerides, 2019)
The following article is based on a keynote speech on Diaspora and Identity in the digital age. Cultural Communities and the Nation delivered at Media Culture Days at the College of Political, Administrative and Communication Sciences, Babeș-Bolyai University, Cluj-Napoca, Romania, on May 17, 2019